(3bUGFOs
(3ChdgG (B:s
(3dbO fGMJ Ydi GdYhO GdbeGQj haGM GdQhV cGdYhO GdbeGQj s
(3BNQgG (B:s
(3hCbU GdBf CLfMI GdebGdI JhbjkG ef GdedGdI adG CQZH EdG dYeQg aj GdEWGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3efg QSGdI GdNjds
(3hQSGdI GdWjQs
(3hef HjfgG TYQ HGdaGQSjI hHChdgG Jedc eDQN (B957(3g```s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B104 s
Keywords: (3GdCOHs